Construction of three-dimensional MnO2/Ni network as an efficient electrode material for high performance supercapacitors. (10th May 2020) - Swain, Nilimapriyadarsini; Mitra, Arjit; Saravanakumar, Balasubramaniam; Balasingam, Suresh Kannan; Mohanty, Smita; Nayak, Sanjay Kumar; Ramadoss, Ananthakumar
Abstract: With the rapid growing interest and the usage of smart electronics devices, a considerable attention has been paid to improve the performance of energy storage devices. Herein, the 3D-MnO2 /Ni electrode was fabricated using hydrogen bubble dynamic template (HBDT)-assisted electrodeposition method, in which several Ni nanoparticles were interconnected, arranged perpendicular to the substrate and formed the dendritic nanowall structure (3D-Ni current collector). This unique microstructure provides numerous of open pores, conductive network, more number of electroactive surface sites for the enhanced charge storage properties. The as-prepared 3D-MnO2 /Ni network exhibited a high specific capacitance of 370 F g −1 (295 mF cm −2 ) at 5 mV s −1 with a remarkable rate capability compared to the MnO2 /Ni. In addition, the 3D-MnO2 /Ni electrode displays excellent long-term stability preserving a capacitance retention of 97% and a coulombic efficiency of 100% even after 5000 cycles. The present results demonstrate that the binder and conductive additive-free 3D architecture porous electrode opens up a new avenue in the fabrication of high surface area porous electrodes for high-performance supercapacitors. Graphical abstract: Image 10395 Highlights: A highly-porous, binder free 3D-MnO2 /Ni nanostructures on Ni-sheet was fabricated for supercapacitors. A uniform MnO2 nanosheets grown on a 3D-Ni/Ni via simple electrodeposition. The 3D-MnO2 /Ni electrode exhibited enhanced capacitance, high rate capability and, better cycling stability. The 3D porous architecture significantly contributed to excellent electrochemical performance.